Dose–volume histogram parameters of high-dose-rate brachytherapy for Stage I–II cervical cancer (≤4cm) arising from a small-sized uterus treated with a point A dose-reduced plan - Nakagawa, Akiko (Oxford University Press, 2014)
We investigated the rectal dose-sparing effect and tumor control of a point A dose-reduced plan in patients with Stage I–II cervical cancer (≤4 cm) arising from a small-sized uterus. Between October 2008 and August 2011, 19 patients with Stage I–II cervical cancer (≤4 cm) were treated with external beam radiotherapy (EBRT) for the pelvis and CT-guided brachytherapy. Seven patients were treated with brachytherapy with standard loading of source-dwell positions and a fraction dose of 6 Gy at point A (conventional brachy-plan). The other 12 patients with a small uterus close to the rectum or small intestine were treated with brachytherapy with a point A dose-reduction to match D2cc of the rectum and <6 Gy as the dose constraint (‘point A dose-reduced plan’) instead of the 6-Gy plan at point A (‘tentative 6-Gy plan’). The total doses from EBRT and brachytherapy were added up and normalized to a biological equivalent dose of 2 Gy per fraction (EQD2). The median doses to the high-risk clinical target volume (HR-CTV) D90 in the conventional brachy-plan, tentative 6-Gy plan and point A dose-reduced plan were 62 GyEQD2, 80 GyEQD2 and 64 GyEQD2, respectively. The median doses of rectal D2cc in the corresponding three plans were 42 GyEQD2, 62 GyEQD2 and 51 GyEQD2, respectively. With a median follow-up period of 35 months, three patients developed Grade-1 late rectal complications and no patients developed local recurrence. Our preliminary results suggested that CT-guided brachytherapy using an individualized point A dose-reduced plan might be useful for reducing late rectal complications while maintaining primary tumor control.